Toxicidade aguda do sulfato de cobre e do triclorfon para três espécies de daphnias em presença e ausência de sedimento - Romero Arauco, Luis Ricardo [UNESP] (Universidade Estadual Paulista (Unesp), 2002)
The aim of this study was to determine the acute toxicity, LE50-48h, of copper sulfate and of trichlorfon, to compare sensitivities and to evaluate the risk of environmental poisoning for three species of daphnias (Daphnia similis, Daphnia magna and Daphnia laevis), in the presence and absence of sediment. The tests for acute toxicity were performed under laboratory conditions, in a climatized room according to standardized methods with some adaptations. The LE50-48h values of copper sulfate calculated for D. magna were 0.345 mg/L with sediment and 0.045 mg/L without sediment; for D. similis, 0.282 mg/L with sediment and 0.042 mg/L without sediment; and for D. laevis 0.140 mg/L with sediment and 0.107 mg/L without sediment. The LE50-48h values of trichlorfon calculated for D. magna were 299.70 ng/L with sediment and 0.70 without sediment; for D. similis, 381.62 with sediment and 0.52 ng/L without sediment; and for D. laevis, 282.72 ng/L with sediment and 0.92 ng/L without sediment. Trichlorfon was more toxic than copper sulfate for the three species of daphnias. Sediment diminished the toxicity of both trichlorfon and copper sulfate for the three species of daphnias. In the absence of sediment, D. magna and D. similis did not show any difference in sensitivity to the two agrochemicals. However, D. laevis was significantly more sensitive than the other two species. In the presence of sediment, there was a difference in sensitivity among the species of daphnias, with D. magna being the most sensitive, followed by D. similis and D. laevis, showing less sensitivity to copper sulfate. In the absence of sediment, the three species of daphnias did not show any difference in sensitivity to trichlorfon. In the presence of sediment, D. magna and D. laevis showed no difference in sensitivity to trichlorfon. The use of copper sulfate and trichlorfon in pisciculture was classified as being of high risk ...

O objetivo deste trabalho foi avaliar a toxicidade aguda CE50-48 h do sulfato de cobre e trichlorfon, comparar a sensibilidade e avaliar o risco de intoxicação ambiental para três espécies de daphnias (D. similis, D. magna e D. laevis) na ausência e presença de sedimento. Os testes de toxicidade aguda foram realizados em condições de laboratório, em sala climatizada de acordo com metodologias normatizadas com algumas adaptações. Os valores de CE50-48h calculados para D. magna foram de 0,345 mg de sulfato de cobre /L com sedimento e 0,045 sem sedimento; para D. similis, 0,282 com sedimento e 0,042 sem sedimento e para D. laevis, 0,140 com sedimento e 0,107 sem sedimento. Os valores de CE50- 48h calculados para D. magna foram de 299,70 hg de trichlorfon /L com sedimento e 0,70 sem sedimento; para D. similis, 381,62 com sedimento e 0,52 sem sedimento e para D. laevis, 282,72 com sedimento e 0,92 sem sedimento. O trichlorfon foi mais tóxico que o sulfato de cobre para as três espécies de daphnias. O sedimento reduziu significativamente a biodisponibilidade do trichlorfon e do sulfato de cobre na água de cultivo para as três espécies de daphnias. Em ausência de sedimento, a Daphnia magna e a Daphnia similis não apresentam diferença de sensibilidade aos dois agrotóxicos, mas a Daphnia laevis foi significativamente mais sensível que as outras duas espécies. Na presença do sedimento houve diferença de sensibilidade entre as espécies de daphnia, sendo a Daphnia magna mais sensível, seguida pela Daphnia similis e Daphnia laevis, que apresentou a menor sensibilidade ao sulfato de cobre. Na ausência do sedimento, as três espécies de daphnia não apresentam diferença de sensibilidade ao trichlorfon. Na presença do sedimento, a Daphnia magna e a Daphnia laevis não apresentam diferença de sensibilidade ao trichlorfon. O uso do sulfato de cobre e trichlorfon na piscicultura...
Keywords: Plantas aquaticas; Toxicidade - Testes; Triclorfon; Toxicidade Aguda; Produtos químicos agrícolas; Agricultural chemicals